High accuracy of a simplified, practical algorithm in a differentiating Crohn’s disease from Intestinal Tuberculosis - hilmi, ida normiha; Nik Muhamad Affendi, Nik Arsyad; Shahrani, Shahreedhan; Mohamed Talha, Abdul Malik; Leow, alex hwong-ruey; Xin Hui, Khoo (S. Karger AG, 2023)
Background: The differentiation between intestinal tuberculosis (ITB) and Crohn’s disease (CD) remains a challenge, particularly in areas where tuberculosis is highly prevalent. Previous studies have identified features that favour one diagnosis over the other. The aim of the study was to determine the accuracy of a standardized protocol in the initial diagnosis of CD versus ITB. Methods: All patients with suspected ITB or CD were prospectively recruited. A standardized protocol was applied, and the diagnosis was made accordingly. The protocol consists of history and examination, ileocolonoscopy with biopsies, and tuberculosis workup. The diagnosis of probable ITB was made based on at least one positive finding. All other patients were diagnosed as probable CD. Patients were treated either with anti-tubercular therapy or steroids. Reassessment was then carried out clinically, biochemically, and endoscopically. In patients with suboptimal response, the treatment was either switched or escalated depending on the reassessment. Results: 164 patients were recruited with final diagnosis of 30 (18.3%) ITB and 134 (81.7%) CD. 1 (3.3%) out of 30 patients with ITB was initially treated as CD. 16 (11.9%) out of 134 patients with CD were initially treated as ITB. The initial overall accuracy for the protocol was 147/164 (89.6%). All patients received the correct diagnosis by 12 weeks after reassessment. Conclusion: In our population, most patients had CD rather than ITB. The standardized protocol had a high accuracy in differentiating CD from ITB.